2016
DOI: 10.5021/ad.2016.28.2.205
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Androgenetic Alopecia Severity with Epicardial Fat Thickness

Abstract: BackgroundAndrogenetic alopecia (AGA) is the most commonly encountered baldness pattern in men. Epicardial fat tissue is found on the cardiac surface between the myocardium and visceral pericardium. Both AGA and epicardial fat thickness (EFT) are related to coronary artery disease, which is also reflected by an increase in carotid intima media thickness (CIMT).ObjectiveThe purpose of this study was to investigate the relation of AGA severity with EFT.MethodsOne hundred twenty-six male patients with AGA aged 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…In addition, testosterone correlated positively and significantly with EFT. Colgecen et al (44) reported that subjects in advanced stages of androgenetic alopecia had higher echocardiographically measured EFT than controls. Moreover, Cakir et al (45) reported a strong positive correlation between testosterone concentrations and EFT in patients with polycystic ovarian disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, testosterone correlated positively and significantly with EFT. Colgecen et al (44) reported that subjects in advanced stages of androgenetic alopecia had higher echocardiographically measured EFT than controls. Moreover, Cakir et al (45) reported a strong positive correlation between testosterone concentrations and EFT in patients with polycystic ovarian disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Norwood-Hamilton baldness scale [7] was utilized to classify the patients into three groups. AGA stages II and IIa were categorized as mild; AGA stages III, IIIa, III vertex, IV, IVa, V, and Va were moderate; and AGA stages VI and VII were classified as severe [8].…”
Section: Methodsmentioning
confidence: 99%
“…Ertas et al examined 51 men with androgenetic alopecia, which began before they turned 30, and described a significantly higher IMT values in patients with alopecia affecting the vertex of the scalp [12]. An analysis of Colgecen et al showed a positive correlation between the IMT and androgenetic alopecia [13].…”
Section: Miażdżycamentioning
confidence: 99%
“…przebadali 51 mężczyzn z łysieniem androgenowym, które rozpoczęło się przed 30. rokiem życia, i stwierdzili znacznie większą wartość wskaźnika IMT u pacjentów z łysieniem w okolicy wierzchołkowej [12]. Analiza, którą przeprowadzili Colgecen i wsp., wykazała dodatnią korelację pomiędzy wskaźnikiem IMT a łysieniem androgenowym [13].…”
Section: Arterial Hypertensionunclassified